Autophagy Enhancing Contributes to the Organ Protective Effect of Alpha-Lipoic Acid in Septic Rats - Jia, Jia; Gong, Xiaoying; Zhao, Yang; Yang, Zhenyu; Ji, Kaiqiang; Luan, Ting; Zang, Bin; Li, Guofu (Frontiers in Immunology, 2019)
Alpha-lipoic acid (ALA) reportedly has protective effects against sepsis, which is a leading cause of mortality worldwide and is associated with multiple organ dysfunction. The present study aimed to investigate further the possible action mechanisms of ALA. Male Sprague-Dawley rats were subjected to cecal ligation and puncture (CLP) in order to establish a sepsis model. The rats received an oral gavage of 200 mg/kg ALA or saline immediately after surgery. The heart rate (HR), left ventricular systolic pressure (LVSP), left ventricular end-diastolic pressure (LVEDP) and maximum rising and lowering rates of left ventricular pressure (±dp/dt) were examined for assessing the cardiac function. Blood urea nitrogen (BUN) and serum creatinine levels were assessed for evaluating renal function. Neutrophil gelatinase-associated lipocalin (NAGL) was examined for reflecting acute renal injury. Histopathological alterations of the small intestine were examined by hematoxylin-eosin staining. The ultrastructure of the small intestine and kidney was observed under electron microscopy. The levels of autophagy- and inflammation-associated proteins were determined via western blot analysis. The binding of nuclear factor-kappa B (NF-κB) to DNA was tested via an electrophoretic mobility shift assay. Cell apoptosis was examined using TUNEL staining. ALA treatment improved the survival rate, restored the loss of body weight and pro-inflammatory cytokines production in the serum of CLP-induced septic rats. ALA improved the cardiac and renal functions, downregulated the expression levels of interleukin-1β, tumor necrosis factor-α, and inducible nitric oxide synthase in the myocardium and small intestine of septic rats. ALA treatment also inactivated the NF-κB signaling pathway in the small intestine. An examination of autophagy showed that ALA increased the LC3II/I ratio, upregulated Atg5, Atg7, and beclin-1 and downregulated p62 protein levels in the myocardium, kidney, and small intestine of septic rats, and further promoted autophagosome accumulation in the kidney and small intestine. In addition, ALA could also reduce cell apoptosis in myocardium, kidney and small intestine tissues. These effects can be completely or party inhibited by 3-MA. Our findings suggest that autophagy enhancing may contribute to the organ protective effect of ALA in septic rats.